Influence of the sodium hypochlorite on the healing process of the dog's teeth treated in single-visit - Nery, Mauro Juvenal [UNESP]; Gomes Filho, João Eduardo [UNESP]; Holland, Roberto [UNESP]; Souza, Valdir de [UNESP]; Bernabé, Pedro Felício Estrada [UNESP]; Otoboni Filho, José Arlindo [UNESP]; Dezan Junior, Eloi [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Lodi, Carolina Simonetti [UNESP] (My University, 2011)
Introduction: Elimination of bacteria from root canals is essential in the endodontic treatment of necrotic pulp teeth once bacteria not only cause, but also maintain, periapical lesions. Objective: The aim of this study was to analyze, in vivo, the influence of the irrigating solutions (1.0% NaOCl, 2.5% NaOCl, 0.9% sterile saline) in singlevisit treatment of dogs' teeth with chronic periapical lesion. Methods: Forty root canals from three Beagle dogs were left exposed to the oral cavity to allow contamination and formation of the chronic periapical lesion. After that, the root canals were biomechanically prepared. During the instrumentation, three irrigating solutions were used: G1- 2.5% NaOCl; G2- 1.0% NaOCl; G3- 0.9% sterile saline. Control Group (G4) had no treatment and no coronal sealing. The root canals were filled with gutta-percha points and Sealapex. The crown openings were sealed with IRM® and amalgam. After six months, the animals were sacrificed and blocks of tissue histologically processed to be stained with hematoxylin and eosin, or Brown and Brenn. Results: There was no histological difference between the utilization of 1.0% or 2.5% sodium hypochlorite (p>0.05), but between them and sterile saline (p<0.05). Conclusion: It was concluded that the use of irrigating solutions with antibacterial potential (1% or 2.5% sodium hypochlorite) provided more favorable conditions for the healing process.
Keywords: Biocompatibility; Healing process; Irrigating solution; Root canal treatment; Sodium hypochlorite